Presuppositions in Descriptive Utterances on Kawula-Gusti of the Song Ingsun as Alternative Learning Materials for Javanese Language in Junior High Schools - Angelica Wahyu Kartika Budiarti; Sugeng Adipitoyo; Ahmad Rizky Wahyudi (Journal of Pragmatics Research, 2026)
Presupposition in descriptive utterances functions as an effective linguistic strategy for subtly instilling philosophical and theological assumptions, as manifested in the contemporary song "Ingsun" by Sujiwo Tejo. This study aims to examine the forms and functions of presupposition that construct the concept of Kawula-Gusti (Servant-God relationship) in the song's lyrics, and to analyze its relevance as Javanese language teaching material in Junior High Schools. This research employs a descriptive qualitative approach with data collection techniques utilizing listening and note-taking, based on the synthesis of presupposition theories by Stalnaker, Karttunen, and Yule, combined with Austin's locutionary acts and Keraf’s descriptive theory. The findings indicate that the lyrics are dominated by lexical and existential presuppositions which implicitly instill a profound understanding of Dununge (Position), Kuwasane (Authority), and Nuju Gambuhe (Union) of the Kawula-Gusti. The descriptive utterances require the listener's cognitive accommodation to accept theological truths as background facts without rigid indoctrination. These findings have strong pedagogical relevance for Javanese Language learning at the JHS Phase D level within the Merdeka Curriculum framework, particularly for training students' interpretive abilities toward implicit meaning and strengthening character based on the Pancasila Student Profile. However, acknowledging that the reliance on a single culturally and theologically dense text limits generalizability across diverse learner backgrounds, this study recommends extending the analytical framework to multiple Javanese texts of varying genres and difficulty levels to ensure broader applicability and instructional flexibility.